Investigating the antidiabetic efficacy of dairy-derived Lacticaseibacillus paracasei probiotic strains: modulating α-amylase and α-glucosidase enzyme functions - Huligere, Sujay S.; Kumari V B, Chandana; Desai, Sudhanva M.; Wong, Ling Shing; Firdose, Nagma; Ramu, Ramith (Frontiers in Microbiology, 2023)
The current study aims to evaluate and characterize the probiotic andantidiabetic properties of lactic acid bacteria (LAB) obtained from milk and other dairy-based products. The strains were tested physiologically, biochemically, and molecularly. Based on biochemical tests and 16S rRNA gene amplification and sequencing, all three isolates RAMULAB18, RAMULAB19, and RAMULAB53 were identified as Lacticaseibacillus paracasei with homology similarity of more than 98%. The inhibitory potential of each isolate against carbohydrate hydrolysis enzymes (α-amylase and α-glucosidase) was assessed using three different preparations of RAMULAB (RL) isolates: the supernatant (RL-CS), intact cells (RL-IC), and cell-free extraction (RL-CE). Additionally, the isolate was evaluated for its antioxidant activity against free radicals (DPPH and ABTS). The strain’s RL-CS, RL-CE, and RL-IC inhibited α-amylase (17.25 to 55.42%), α-glucosidase (15.08–59.55%), DPPH (56.42–87.45%), and ABTS (46.35–78.45%) enzymes differently. With the highest survival rate (>98%) toward tolerance to gastrointestinal conditions, hydrophobicity (>42.18%), aggregation (>74.21%), as well as attachment to an individual’s colorectal cancer cell line (HT-29) (>64.98%), human buccal and chicken crop epithelial cells, all three isolates exhibited extensive results. All three isolates exhibited high resistance toward antibiotics (methicillin, kanamycin, cefixime, and vancomycin), and other assays such as antibacterial, DNase, hemolytic, and gelatinase were performed for safety assessment. Results suggest that the LAB described are valuable candidates for their significant health benefits and that they can also be utilized as a beginning or bio-preservative tradition in the food, agriculture, and pharmaceutical sectors. The LAB isolates are excellent in vitro probiotic applicants and yet additional in vivo testing is required.